CO2 activation and synthesis of cyclic carbonates and alkyl/aryl carbamates over adenine-modified Ti-SBA-15 solid catalysts - Srivastava, R; Srinivas, D; Ratnasamy, P (Journal of Catalysis, 2005)
Cyclic carbonates were synthesized by the cycloaddition Of CO2 to epoxides (epichlorohydrin, propene oxide, and styrene oxide), and carbamates were synthesized by reaction of alkyl or aryl amines, CO2, and n-butyl bromide. Solvents and cocatalysts/promoters, like N,N-dimethylaminopyridine (DMAP) and quaternary ammonium salts, which are usually essential with conventional catalyst systems, could be avoided with the use of adenine-modi lied Ti-SBA-15 catalysts. The catalysts were reused in several recycle experiments. The structural and textural properties of the catalysts were determined by X-ray diffraction (XRD), transmission electron microscopy (TEM), N-2 adsorption, and Fourier transform infrared (FTIR) and diffuse reflectance ultraviolet-visible (UV-vis DRS) techniques. Acid-base properties of the solid catalysts were investigated by temperature-programmed desorption (TPD) of NH3 and CO2 and DRIFTIR spectroscopy of adsorbed pyridine and CO2 techniques. The studies reveal that the Ti4+ ions increase catalytic activity by enhancing the adsorption of the epoxide and alkyl or aryl amine substrates. CO2 molecules are activated at the basic nitrogen groups of adenine. Increasing the surface concentrations of either CO2 (by anchoring basic molecules like adenine or increasing the partial pressure of CO2) or epoxides and alkyl or aryl amines (by increasing the concentration of Lewis acidic Ti4+ ions) enhances the catalytic activity. CO2 molecules activated at the covalently anchored adenine sites react with epoxide/amines adsorbed on the silica surface to form carbonates/carbamates. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: activation of CO2; CO2 fixation; DRIFTIR spectroscopy of adsorbed pyridine and CO2; organo-functionalized mesoporous silica; phosgene-free synthesis; synthesis of carbamates; synthesis of cyclic carbonates; temperature-programmed desorption of NH3 and CO2 titanosilicates; Ti-SBA-15

Factors affecting activation and utilization of carbon dioxide in cyclic carbonates synthesis over Cu and Mn peraza macrocyclic complexes - Srivastava, R.; Bennur, T. H.; Srinivas, D. (Journal of Molecular Catalysis A - Chemical, 2005)
The catalytic activities of several Cu and Mn aza complexes for cyclic carbonate synthesis from CO2 and epoxides are reported. The various factors affecting activation of CO2 by metal complexes and its utilization in cyclic carbonate synthesis have been investigated. Fr-IR, UV-vis and EPR spectroscopic investigations reveal that CO2 coordinates to Cu in eta(1)-C mode of coordination. Nature of the ligand and substitution influence the lability of metal-CO2 bonding. The differences in the catalytic activities are correlated with the mode and strength of CO2 binding. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: benign synthesis; Carbon dioxide; catalysis by Cu and Mn complexes; CO2 activation; CO2 fixation; CO2 utilization; cyclic carbonates; polycarbonates; spectroscopy

Syntheses of polycarbonate and polyurethane precursors utilizing CO2 over highly efficient, solid as-synthesized MCM-41 catalyst - Srivastava, R.; Srinivas, D.; Ratnasamy, P. (Tetrahedron Letters, 2006)
As-synthesized MCM-41 was used as a reusable, heterogeneous catalyst for the eco-friendly synthesis of cyclic carbonate precursors of polycarbonates via a cycloaddition reaction of CO2 with epoxides. This catalyst is also efficient for the synthesis of alkyl and aryl carbamate precursors of polyurethanes via the reaction of amines, CO2 and alkyl halides. Both these reactions were carried out under mild conditions and without using any solvent or co-catalyst. CO2 is utilized as a raw material replacement for toxic phosgene in the conventional synthesis of these chemicals. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: carbamates; carbon dioxide utilization; CO2 fixation; cyclic carbonates; eco-friendly processes; MCM-41; polycarbonates; polyurethanes

Triazine-based organic polymer-catalysed conversion of epoxide to cyclic carbonate under ambient CO2 pressure - Biswas, Tanmoy; Halder, Arjun; Paliwal, Khusboo S.; Mitra, Antarip; Tudu, Gouri; Banerjee, Rahul; Mahalingam, Venkataramanan (Chemistry-An Asian Journal, 2020)
In this work we have achieved epoxide to cyclic carbonate conversion using a metal-free polymeric catalyst under ambient CO2 pressure (1.02 atm) using a balloon setup. The triazine containing polymer (CYA-ANIS) was prepared from cyanuric chloride (CYA-Cl) and o-dianisidine (ANIS) in anhydrous DMF as solvent by refluxing under the N-2 gas environment. The presence of triazine and amine functional groups in the polymer results in the adsorption of CO2 up to 7 cc/g at 273 K. This inspired us to utilize the polymer for the conversion of a series of functionalised epoxides into their corresponding cyclic carbonates in the presence of tetrabutyl ammonium iodide (TBAI) as co-catalyst. The product has wide range of applications like solvent in lithium ion battery, precursor for polycarbonate, etc. The catalyst was efficient for the conversion of different mono and di-epoxides into their corresponding cyclic carbonates under atmospheric pressure in the presence of TBAI as co-catalyst. The study indicates that epoxide attached with electron withdrawing groups (like, CH2Cl, glycidyl ether, etc.) displayed better conversion compared to simple alkane chain attached epoxides. This is mainly due to the stabilization of electron rich intermediates produced during the reaction (e. g. epoxide ring opening or CO2 incorporation into the halo-alkoxide anion). This catalyst mixture was capable to maintain its reactivity up to five cycles without losing its activity. Post catalytic characterization clearly supports the heterogeneous and recyclable nature of the catalyst.
Keywords: CO2 fixation; cyclic carbonates; epoxides; Heterogeneouscatalyst; metal free catalyst; Triazinepolymer

Tunable, amine-functionalized porous silica catalyst for CO2 transformation into cyclic organic carbonates at atmospheric pressure - Gorai, Twinkle; Thanasekar, Chandragopal; Kumar, Pawan; Babu, Athira; Kurungot, Sreekumar; Vinod, C. P. (Chemistry-A European Journal, 2025)
A silica catalyst with characteristic features of broad pore size distribution, large pore width and tunable basic sites was synthesized by a one-step green co-condensation synthesis method analogous to SBA-15 synthesis. The surface chemical features of the above catalyst were explored by XPS, N-2 and CO2 adsorption and desorption experiments. The catalyst showed 90% conversion of styrene oxide (SO) with nearly complete selectivity toward styrene carbonate (SC) in 7 hours under a solvent-free condition at a temperature of 120 degrees C with the aid of co-catalyst tetrabutylammonium bromide (TBAB). Moreover, the catalyst demonstrates versatility with various epoxide substrates, providing valuable insights into the cycloaddition reaction under ambient pressure conditions involving carbon dioxide. The mechanistic details of the catalytic conversion were investigated by the in-situ DRIFT studies and reported here.
Keywords: CO2 fixation; cyclic organic carbonates; heterogeneous catalysis; in-situ FTIR